Pengendalian Kualitas Telur Ayam Pada Proses Penetasan Menggunakan Metode Grafik Kendali T^2 Hotelling Di PT Japfa Comfeed Indonesia Padang Pariaman - Erawati, Sisri; Murni, Dewi (UNIVERSITAS NEGERI PADANG, 2024)
In Padang Pariaman there is PT Japfa Comfeed Indonesia which focuses on breeding chicken eggs. Quality monitoring conducted by the company is still limited to recording the proportion of defective eggs originating from each region. However, the company has not carried out further quality control using statistical methods. This study aims to describe the state of the eggs and see whether the quality of the chicken eggs in the hatching process at the company is under statistical control on the Hotelling control chart. This research was conducted simultaneously which consisted of three correlated variables, namely thin eggs, cracked eggs, and broken eggs. The data obtained is then processed using the Hotelling control chart method. Based on the results of the analysis, it was found that out of the 32 observations, 2 observation points were detected that were out of control (uncontrolled) from the upper limit (BKA) of the control chart. So it can be concluded that in July 2022 to June 2023 the process was not statistically controlled.